Critical Thinking in EFL Academic Writing:A Needs Analysis at the Define Stage of the 5D Model - Yuni Putri Utami; Syafira Alfiani; Laudiya Aurilia Putri (Universitas Islam Ogan Komering Ilir Kayuagung, 2026)
The rapid advancement of artificial intelligence (AI) has significantly altered English language instruction, highlighting the importance of critical thinking (CT) in academic writing. However, CT-oriented writing materials for informatics students in English for Specific Purposes (ESP) contexts remain limited, indicating the importance of a thorough needs analysis to guide content development. This study seeks to examine students’ needs for CT-integrated writing in English materials by applying the 5D Model (Define, Design, Develop, Demonstrate, Deliver). A mixed-methods approach was employed to collect extensive data, including questionnaires, interviews, and curriculum analysis. The findings demonstrate that, while students have a very high level of understanding of critical thinking, their ability to apply it in academic writing is uneven. The Define stage emerged as the most important phase because it clarifies learning demands, establishes instructional goals, and identifies skill gaps. Scaffolding approaches, critical reading exercises, and formative feedback are all important components for lecturers to assist writing development. As these instruments were introduced, students reported higher levels of confidence, conceptual knowledge, and the capacity to develop evidence-based arguments. The findings emphasize the necessity of incorporating critical thinking into writing instruction as a key component of ESP material production, especially in AI-driven learning environments. A comprehensive needs analysis is thus required to ensure that instructional materials properly meet learners' academic needs.